Indapamide microhemodynamic effects in patients with essential arterial hypertension - L. N. Eliseeva; Z. A. Baste; S. P. Oransky; A. Yu. Blednova; Z. A. Avakimyan (Российский кардиологический журнал)
The aim of this study was to investigate microcirculatory (M) changes and andothelin-1 levels in 3-month indapamide treatment. The study included 22patients with essential arterial hypertension (EAH), Stage I-II, and 12 normotensive controls. Microcirculation was assessed by laser Dopplerflowmetry, endothelin-1 level - by enzyme immunoassay method. The EAH patients demonstrated M heterogeneity, with high prevalence of pathologic M types. Indapamide was effective and safe in EAH treatment, improving M status. Serum levels of endothelin-1 correlated with Doppler flowmetric indices - Aa/IM, alpha-rhythm amplitude, as well as with blood pressure levels.